2019
DOI: 10.15835/buasvmcn-vm:2019.0028
|View full text |Cite
|
Sign up to set email alerts
|

Anthelmintic Resistance in Equine Nematodes – A Review on the Current Situation, with Emphasis in Europe

Abstract: Since the introduction of the last equine broad-spectrum anthelmintic group in the 1980’s, the investment in new drugs to control horse’s parasites did not result in new advancements. These drugs allowed a very effective and extensive control of equine nematodes through successful interval dosing programs, firstly introduced in the 1960’s. However, the widespread and indiscriminate use of anthelmintics in these intensive treatments have led to increasing resistance in the major equine nematodes. Reports of red… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 39 publications
1
4
0
Order By: Relevance
“…Mini-FLOTAC had a comparatively better CV% (average < 28.3) and bead recovery average of >65% among the three methods. Our result corroborated the findings of other studies that confirmed less variance for Mini-FLOTAC [28][29][30]. The modified McMaster had a CV% of >40 for all variants except ZnSO 4 and improved recovery of >90% for all variants except NaNO 3 .…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Mini-FLOTAC had a comparatively better CV% (average < 28.3) and bead recovery average of >65% among the three methods. Our result corroborated the findings of other studies that confirmed less variance for Mini-FLOTAC [28][29][30]. The modified McMaster had a CV% of >40 for all variants except ZnSO 4 and improved recovery of >90% for all variants except NaNO 3 .…”
Section: Discussionsupporting
confidence: 92%
“…For the modified McMaster method, most replicates tended to disperse away from the slope. However, many replicates overestimated spiked beads, indicating a potential threat of false counts [29]. The modified Wisconsin method variants performed better in counting the lower bead standards whereas the higher ones tended to disperse away from the slope.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…The status of anthelmintic resistance in equine nematodes has been reviewed multiple times over the past couple of decades ( Kaplan, 2002 , 2004 ; von Samson-Himmelstjerna, 2012 ; Matthews, 2014 ; Peregrine et al, 2014 ; Silva et al, 2019 ). However, several new developments reported in the past decade prompts a new review.…”
Section: Introductionmentioning
confidence: 99%
“…This has inevitably selected for anthelminthic resistance, and, not surprisingly, resistance to drugs is now commonly observed, especially in cyathostomins [3]. Controlling these strongyles with the currently used molecules is therefore more difficult [4]. In addition, although treating equine infections is necessary for animal health, the use of anthelmintic drugs has been associated with an increased risk of developing colic in the week following an anthelminthic treatment [5].…”
Section: Introductionmentioning
confidence: 99%